2021
DOI: 10.1186/s42269-021-00670-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on ER stress-induced apoptosis pathway in cervical cancer HeLa cells treated with biosynthesized gold nanoparticles

Abstract: Background The expression of apoptotic family of protein plays a major role in induction of programmed cell death. There are six major apoptotic proteins such as Caspase 12, Bcl 2, BAX, Cytochrome c, PARP3 and Mcl1. All these proteins have crucial role in the regulation of apoptosis through mitochondrial degradation, DNA damage, nuclear condensation and eventually cell death of the cancerous cells. It was observed that the apoptotic pathway has been initiated in the cancer cells from the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…These ROS can be generated when AuNPs are taken up by cells, and they can cause DNA damage through a variety of mechanisms. Several studies have revealed the capability of AuNPs to induce caspase mediated apoptosis pathway [46][47][48] .This study measured cell DNA damage using comet assay, which is known for its simplicity and speed 49 , ability to detect DNA damage in a variety of cell types 50 , and qualitative and quantifiable index to evaluate DNA damage 51 . Electrophoresis transports damaged DNA out of the cell, generating a comet tail.…”
Section: Discussionmentioning
confidence: 99%
“…These ROS can be generated when AuNPs are taken up by cells, and they can cause DNA damage through a variety of mechanisms. Several studies have revealed the capability of AuNPs to induce caspase mediated apoptosis pathway [46][47][48] .This study measured cell DNA damage using comet assay, which is known for its simplicity and speed 49 , ability to detect DNA damage in a variety of cell types 50 , and qualitative and quantifiable index to evaluate DNA damage 51 . Electrophoresis transports damaged DNA out of the cell, generating a comet tail.…”
Section: Discussionmentioning
confidence: 99%